Levothyroxine therapy and its impact on serum lipids: Addressing dyslipidemia in hypothyroidism - Rohit Kumar Gupta; Rajeev Verma; Manisha Verma; Anirudh Mukherjee; Pramod Kumar; Mahendra Kumar Meena; Manu Sharma (Journal of Family Medicine and Primary Care, 2025)
Background and Objective: The major goal of this study was to analyse the influence of levothyroxine medication on serum lipid levels in individuals with hypothyroidism, as well as its efficacy in controlling dyslipidemia caused by thyroid hormone deficiencies. This method provides a complete assessment of therapy efficacy and aids in identifying factors that may influence treatment results. Methodology: This prospective observational study, conducted from September 2019 to October 2020 at Shri Shiv Prasad Gupt Divisional District Hospital in Varanasi, India, included 150 patients with newly diagnosed hypothyroidism. A predesigned proforma was used in the study to collect demographic and medical history information. The data were analysed using SPSS version 23. Results: The study of 150 newly diagnosed hypothyroidism patients, predominantly aged 31–40 years and with a significant female predominance (95.4%), found a notable age and gender distribution in subclinical versus overt hypothyroidism. Subclinical cases were all female and concentrated in the 31–40 age group, while overt hypothyroidism was more evenly distributed, with a higher prevalence in the same age group and extending to older ages. TSH levels were significantly higher in overt hypothyroidism (45.1 ± 30.4 μU/mL) compared to subclinical hypothyroidism (8.6 ± 0.82 μU/mL, P < 0.01), reflecting more severe thyroid dysfunction in overt cases. Levothyroxine therapy improved lipid profiles in both conditions: In subclinical hypothyroidism, total cholesterol and triglycerides decreased and HDL increased; in overt hypothyroidism, total cholesterol, triglycerides, and LDL decreased, while HDL increased significantly. Levothyroxine also effectively normalized TSH levels in both subclinical (8.6 ± 0.8 μU/mL to 2.9 ± 1.33 μU/mL) and overt hypothyroidism (45.1 ± 30.4 μU/mL to 3.5 ± 1.1 μU/mL), demonstrating its efficacy in managing thyroid function and associated dyslipidemia. Conclusion: The study found that levothyroxine therapy significantly improved lipid profiles and reduced TSH levels in both subclinical and overt hypothyroidism. Despite these positive outcomes, the small sample size and short duration suggest the need for further research with a larger cohort and longer follow-up to validate and expand on these findings.